The investigation of CD4+T-cell functions in primary HIV infection with antiretroviral therapy. Issue 28 (July 2017) - Sun, Yu; Fu, Yajing; Zhang, Zining; Tang, Tian; Liu, Jing; Ding, Haibo; Han, Xiaoxu; Xu, Junjie; Chu, Zhenxing; Shang, Hong; Jiang, Yongjun
Abstract : Abstract: Human immunodeficiency virus (HIV) infection leads to reduced CD4 + T-cell counts and immune dysfunction. Initiation of antiretroviral therapy (ART) in HIV primary infection has been recommended to achieve an optimal clinical outcome, but a comprehensive study on restoration of CD4 + T-cell function in primary HIV-infected individuals with ART still needs to be eluciated. We investigated longitudinal changes in the CD4 + T-cell counts, phenotypes, and functions in HIV-infected individuals with early ART (initiated within 6 months after HIV infection) or later ART (initiated more than 12 months after HIV infection). Patients from early ART and later ART groups had received ART for at least 1 year. Individuals with early ART had more CD4 + T cells, a faster rate of CD4 + T-cell recovery than those receiving later ART; the levels of CD4 + T-cell activation and senescence were lower in early ART compared to those with later ART ( P = .031; P = .016), but the activation was higher than normal controls (NC) ( P = .001); thymic emigrant function was more upregulated in early ART than in later ART ( P = .015), but still lower than NC ( P = .027); proliferative capacity and interferon-γ secretion of CD4 + T cells were significantly decreased in primary infection ( P < .001; P = .029), and early ART restored these CD4 + T-cell functions, there is no difference with NC, later ART could partially restore the functions of CD4 + T cells, but it remained lower than that of NC ( P = .005; P = .019). Early ART could better improve CD4 + T-cell function.